DECISION SUPPORT SYSTEM FOR SELECTING THE BEST LECTURER USING THE WEIGHTED PRODUCT METHOD: SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN DOSEN TERBAIK MENGGUNAKAN METODE WEIGHTED PRODUCT - Itin Riati; Wahyu Prima; Gunawan Ali (Perkumpulan Doktor Indonesia Maju (PDIM), 2023)
The process of determining the best lecturers must comply with predetermined criteria. To assist in selecting a person who deserves to be the best lecturer, a decision support system is needed. One method that can be used for a decision support sys tem is using the Weighted Product (WP) method by considering the criteria and weights. This method was chosen because it is able to choose the best alternative, namely the best lecturer based on the criteria entered, then look for the weight value of eac h attribute, after the process of looking for rankings to get the best alternative, namely the best lecturer. The WP method is used in determining the best alternative or the order of importance of alternatives. The results of this study are a web -based system developed using sublime text that can be used by admins to manage lecturer data, criteria and alternatives. The system output displays the alternative order of lecturers as the best le The WP method is used in determining the best alternative or the order of importance of alternatives. The results of this study are a web-based system developed using sublime text that can be used by admins to manage lecturer data, criteria and alternatives. The system output displays the alternative order of lecturers as the best lecturer recommendations at the Universitas Dharmas Indonesia.